1995
DOI: 10.1577/1548-8675(1995)015<0480:smoabt>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Movements of Adult Brown Trout Relative to Temperature in a Coolwater Reservoir

Abstract: Seasonal movements of 16 large (>400 mm total length) brown trout Salmo trutta were monitored for 216–347 d by means of radio telemetry techniques in Box Canyon Reservoir, Washington. In 1992, radio‐tagged fish moved out of the reservoir in late June when water temperatures reached 19–20°C and inhabited tributary streams containing water below 16°C. However, similar movements into tributary streams were not observed in 1993 when reservoir water temperatures were somewhat cooler. Diel tracking of fish in July–A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 0 publications
3
13
0
Order By: Relevance
“…In rivers, sea-son, light intensity, water levels and water temperature, in particular, have been shown to influence the timing and intensity of movement (Heggenes 1988;Jonsson 1991;Garrett & Bennett 1995;Rustadbakken et al 2004). In rivers, sea-son, light intensity, water levels and water temperature, in particular, have been shown to influence the timing and intensity of movement (Heggenes 1988;Jonsson 1991;Garrett & Bennett 1995;Rustadbakken et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In rivers, sea-son, light intensity, water levels and water temperature, in particular, have been shown to influence the timing and intensity of movement (Heggenes 1988;Jonsson 1991;Garrett & Bennett 1995;Rustadbakken et al 2004). In rivers, sea-son, light intensity, water levels and water temperature, in particular, have been shown to influence the timing and intensity of movement (Heggenes 1988;Jonsson 1991;Garrett & Bennett 1995;Rustadbakken et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…1990; Meyers et al. 1992; Garrett & Bennett 1995). Results from several studies have indicated that resident stream trout exhibit relatively limited movement (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…On the West Kill, 79,098 m 2 were mapped and 0.085% (67 m 2 ) and 0.018% (14 m 2 ) were BMT by 1 and 2 C, respectively. Considering that previous studies identified cold-water refuges as areas at least 3 C colder than the surrounding water (Garrett & Bennett 1995;Ebersole et al 2001;Ebersole et al 2003a), these data strongly suggest that the Upper Schoharie and West Kill lack adequate thermal refuge. Additionally, the value of a refuge area is not only defined by its temperature relative to ambient river water, but also by its quality, size, and accessibility (Dunning et al 1992;Townsend et al 1997;Ebersole et al 2003b).…”
Section: Thermal Infrared Temperaturesmentioning
confidence: 53%